Firefly Meta-Heuristic Algorithm for Training the Radial Basis Function Network for Data Classification and Disease Diagnosis - Horng, Ming-Huwi; Lee, Yun-Xiang; Lee, Ming-Chi; Liou, Ren-Jean (IntechOpen, 2012)
None